Penerapan Sistem Informasi Akuntansi Terhadap Efektivitas Pengendalian Internal Kas Pada Usaha Peternak Ayam Broiler Di Kabupaten Labuhanbatu Selatan - Desi Lestari; Nurbaiti Nurbaiti; Arnida Wahyuni Lubis (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the application of accounting information systems to the effectiveness of cash internal control in broiler chicken farming businesses in South Labuhanbatu Regency and to determine the effectiveness of cash internal control in broiler chicken farming businesses in South Labuhanbatu Regency which is running effectively. The type of research used in this research is descriptive qualitative research. The type of data used in this research is primary data and secondary data obtained from broiler chicken farming businesses in South Labuhanbatu Regency. Data collection techniques were carried out using documentation and interview techniques. The results of this research indicate that the application of the accounting information system to the effectiveness of internal cash control in broiler chicken farming businesses in South Labuhanbatu Regency is considered effective, however, there are still shortcomings in the system which still exist in some manual parts. The effectiveness of internal cash control does not fully use computers but there are still manual ones, and the obstacles experienced when recording financial reports in broiler chicken farming businesses in South Labuhanbatu Regency are that sometimes it is still difficult for outside parties to accept and understand because they do not fully use the system. accounting information.